2008
DOI: 10.1038/npp.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Analysis of Genes Implicated in Rodent Models of Antidepressant Response: Association of TREK1 and Treatment Resistance in the STAR*D Study

Abstract: Recent rodent models of antidepressant response implicate a novel set of genes in mechanisms of antidepressant action. The authors examined variants in four such genes (KCNK2 (TREK1), SLC18A2 (VMAT2), S100A10, and HDAC5) for association with remission in a large effectiveness trial of antidepressant treatments. Subjects were drawn from the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study, a multicenter, prospective, effectiveness trial in major depressive disorder (MDD). Outpatients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 49 publications
4
67
1
1
Order By: Relevance
“…Novel associations with citalopram response were reported within HTR2A (the gene that encodes the serotonin 2A receptor) (32) and GRIK4 (encodes the KA1 subunit of the glutamate-kainate receptor) (35). The KCNK2 gene (encodes a potassium channel of the K subfamily) was associated with treatment resistance (31). …”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel associations with citalopram response were reported within HTR2A (the gene that encodes the serotonin 2A receptor) (32) and GRIK4 (encodes the KA1 subunit of the glutamate-kainate receptor) (35). The KCNK2 gene (encodes a potassium channel of the K subfamily) was associated with treatment resistance (31). …”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%
“…On the basis of rodent models of anti-depressant response, Perlis and colleagues (31) examined variants in four genes—KCNK2 (TREK1), SLC18A2 (VMAT2), S100A10, and HDAC5—for association with treatment resistance in STAR * D, which they defined as not achieving remission despite two adequately tolerated treatment trials (that is, levels 1 and 2). The remission phenotype was defined as a QIDS-C score <6.…”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, an increased risk were found for the methylenetetrahydrofolate reductase MTHFR C677T polymorphism (pooled OR, 1.36), the guanine nucleotide binding protein 3 GNB3 C825T variant (pooled OR, 1.38; CI, 1.13-1.69), and the dopamine transporter SLC6A3 40 bp VNTR (pooled OR, 2.06; CI, 1.25-3.40) (Lopez-Leon et al, 2008). Pharmacogenetic studies of antidepressants in the STAR*D trial have identified genes associated with treatment response (Hu et al, 2007;Lekman et al, 2008a;McMahon et al, 2006;Paddock, 2008), treatment resistance (Perlis et al, 2008), and treatment-emergent suicidal ideation (Laje et al, 2009;Laje et al, 2007;Perlis et al, 2007). In addition, polymorphisms in genes that encode drug-metabolizing enzymes and transporters have been tested for correlation with treatment response (Peters et al, 2008).…”
Section: Genetic Predictors Of Depression and Antidepressant Responsementioning
confidence: 99%
“…Deletion of the TREK-1 gene (also called kcnk2) results in a depression-resistant phenotype that mimics treatment with antidepressants (Heurteaux et al, 2006). Interestingly, the Star*D study has identified an association between the existence of four genetic variants (SNPs) in the TREK-1 locus, and a resistance to multiple antidepressant classes (Perlis et al, 2008;Dillon et al, 2010). All these findings indicate that 1) genetic variations in TREK-1 may identify individuals at risk for depression treatment resistance and 2) a search of selective blockers of TREK-1, hitherto not available, might potentially lead to a new generation of antidepressants.…”
mentioning
confidence: 99%